Problems of Legal Regulation Improvement in the Sphere of Science, Technology and Innovation in Post-Soviet Space in Keeping with Modern International Regulatory Trends - GUTNIKOV, Oleg V.; DUPAN, Anna S.; EMELYANTSEV, Vladimir P. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The article analyzes main international regulatory trends in science, technology and innovation (STI) formalized in the documents of the UN, OECD, UNESCO and other international organizations. These trends include (1) STI development as an integral part of sustainable development, (2) focus on science education and STI promotion, (3) STI strategic planning and foresight, (4) establishing terms of STI monitoring, (5) Open Science and recognition of information and communication technology (ICT) as a driving force of Open Science and innovation, (6) focus on fundamental research in significant socioeconomic projects, (7) new approaches to the innovation support. These international STI regulatory trends are not reflected in the current Russian legislation. Due to the critical need of advanced regulation in the Russian legal and economic system, the new STI Law should include all the abovementioned international trends while the Ministry of Education and Science of the Russian Federation are drafting its Concept. In this article, the authors put forward proposals on the content of norms reflecting the relevant international trends that can be used in developing the abovementioned federal Law.